2019
DOI: 10.1002/tox.22869
|View full text |Cite
|
Sign up to set email alerts
|

p,p′‐Dichlorodiphenyltrichloroethane promotes aerobic glycolysis via reactive oxygen species–mediated extracellular signal‐regulated kinase/M2 isoform of pyruvate kinase (PKM2) signaling in colorectal cancer cells

Abstract: Aerobic glycolysis is crucial to tumor cells to acquire energy for proliferation and metastasis. Dichlorodiphenyltrichloroethane (DDT), which is a persistent organic pollutant, has been associated with colorectal cancer (CRC) progressions, but the influence of p,p 0 -DDT on CRC cell metabolism remains unclear. This study showed that exposure to low concentrations of p,p 0 -DDT from 10 −11 to 10 −7 M for 48 hours significantly increased glucose uptake and lactate production in colorectal adenocarcinoma cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…However, the main way to acquire energy in cancer cells is aerobic glycolysis even under the condition of adequate oxygen. Accumulated evidence suggests there are numerous glucose metabolism-associated ncRNAs dysregulated in cancers resulting in mitochondrial dysfunction, abundant activation of key enzymes, altered isozyme profiles and dysregulated glucose metabolic signalling pathways [ 64 66 ]. Current progress in the role of ncRNAs in glucose metabolism has been summarized in Fig.…”
Section: Ncrnas Affect Cancer Progression Through Metabolic Reprogram...mentioning
confidence: 99%
“…However, the main way to acquire energy in cancer cells is aerobic glycolysis even under the condition of adequate oxygen. Accumulated evidence suggests there are numerous glucose metabolism-associated ncRNAs dysregulated in cancers resulting in mitochondrial dysfunction, abundant activation of key enzymes, altered isozyme profiles and dysregulated glucose metabolic signalling pathways [ 64 66 ]. Current progress in the role of ncRNAs in glucose metabolism has been summarized in Fig.…”
Section: Ncrnas Affect Cancer Progression Through Metabolic Reprogram...mentioning
confidence: 99%
“…Xiangyun et al [55] have also reported that high concentrations of ROS can decrease both the succinylation and activity of PKM2 by increasing its binding to SIRT5. Furthermore, ROS can not only affect the expression level and localization of PKM2 but also mediate the crosstalk between PKM2 and other enzymes, including apurinic/apyrimidinic endonuclease (APE1) and ectonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2) [56,57]. While another study has shown that the PKM2 mRNA is not inhibited by ROS, the decrease of PKM2 expression is caused by PKM2 degradation.…”
Section: Pkm2 and The Regulation Of Mitochondrial Rosmentioning
confidence: 99%
“…Aerobic glycolysis is typical in the metabolic reprogramming of CRC. Abnormal glucose metabolism in CRC cells is primarily attributed to the mitochondrial dysfunction, abundant activation of key enzymes involved in glycolysis, altered isozyme profiles and dysregulated glucose metabolic signaling pathways ( 12 , 13 ).…”
Section: Regulation Of Glucose Metabolic Reprogramming By Mirnasmentioning
confidence: 99%